A survey of technologies on the rise for emotion-enhanced interaction. (December 2015) - Cernea, Daniel; Kerren, Andreas
Abstract: Emotions are a major part of the human existence and social interactions. Some might say that emotions are one of the aspects that make us truly human. However, while we express emotions in various life settings, the world of computing seems to struggle with supporting and incorporating the emotional dimension. In the last decades, the concept of affect has gotten a new upswing in research, moving beyond topics like market research and product development, and further exploring the area of emotion-enhanced interaction. In this paper, we highlight techniques that have been employed more intensely for emotion measurement in the context of affective interaction. Besides capturing the functional principles behind these approaches and the inherent volatility of human emotions, we present relevant applications and establish a categorization of the roles of emotion detection in interaction. Based on these findings, we also capture the main challenges that emotion measuring technologies will have to overcome in order to enable a truly seamless emotion-driven interaction. Abstract : Highlights: We highlight techniques for emotion measurement in context of affective interaction. We present and categorize affective interactional systems and applications. Main research challenges of emotion measuring technologies are discussed.